Transformational leadership and field-level accountability in smallholder beef cattle development under environmental uncertainty - FERDI FATHUROHMAN; TITIK EKOWATI; SIWI GAYATRI; RETNO ADIWINARTI; INA NURTANTI; NEFI ANDRIANA FAJRI; NURUL MUKMINAH; RAHMI RAHMAWATI (Smujo International, 2026)
Abstract. Fathurohman F, Ekowati T, Gayatri S, Adiwinarti R, Nurtanti I, Fajri NA, Mukminah N, Rahmawati R. 2026. Transformational leadership and field-level accountability in smallholder beef cattle development under environmental uncertainty. Asian J Agric 10 (1): g100143. https://doi.org/10.13057/asianjagric/g100143. Accountability within Indonesia’s smallholder beef cattle development program (SIKOMANDAN) is crucial for ensuring national meat security, yet program implementation frequently faces complex field-level challenges such as biological risks and resource instability. This study investigates the institutional determinants of program accountability, focusing on the direct effects of System Integrity (SI), Internal Control Systems (ICS), and Transformational Leadership (TL), alongside the moderating roles of Organizational Commitment (OC) and Environmental Uncertainty (EU). A quantitative survey was conducted using a purposive sampling technique in Subang District, West Java, Indonesia, involving 125 local government officials and agricultural extension workers. Empirical data were evaluated using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test both direct and interaction effects. The results show that Transformational Leadership (β = 0.458, p < 0.001) and System Integrity (β = 0.392, p < 0.001) significantly enhance accountability, with the model explaining 76.4% of variance (R² = 0.764). In contrast, the Internal Control System has no significant direct effect (β = -0.017, p = 0.814). Organizational Commitment emerges as a significant independent predictor (β = 0.512, p < 0.001) rather than a moderator. Environmental Uncertainty shows no direct effect but indicates a borderline negative effect on internal controls (β = -0.135, p = 0.058). These findings highlight that accountability in livestock governance is driven more by leadership and system integrity than by formal control mechanisms alone. Strengthening adaptive governance through leadership development and flexible operational procedures is essential for program effectiveness in volatile agricultural contexts.